Children's Health Insurance Program Expansions: What Works for Families? - E. Kathleen Adams PhD; Emily M. Johnston PhD; Gery Guy PhD; Peter Joski MS; Patricia Ketsche PhD (SAGE Publishing, 2019)
We examine the impact of Children's Health Insurance Program (CHIP) eligibility expansions 1999 to 2012 on child and joint parent/child insurance coverage. We use changes in state CHIP income eligibility levels and data from the Current Population Survey Annual Social and Economic Supplement to create child/parent dyads. We use logistic regression to estimate marginal effects of eligibility expansions on coverage in families with incomes below 300% federal poverty level (FPL) and, in turn, 150% to 300% FPL. The latter is the income range most expansions targeted. We find CHIP expansions increased public coverage among children in families 150% to 300% FPL by 2.5 percentage points (pp). We find increased joint parent/child coverage of 2.3 pp ( P = .055) but only in states where the public eligibility levels for parent and child are within 50 pp. In these states, the CHIP expansion increased the probability that both parent/child are publicly insured (2.5 pp) among insured dyads, but where the eligibility levels are further apart (51-150 pp; >150 pp), CHIP expansions increase the probability of mixed coverage-one public, one private-by 0.9 to 1.5 pp. Overall, families made decisions regarding coverage that put the child first but parents took advantage of joint parent/child coverage when eligibility levels were close. Joint public parent/child coverage can have positive care-seeking effects as well as reduced financial burdens for low-income families.